Masalah Sosial Pelajar dan Hubungannya dengan Kemerosotan Pembelajaran - Ali, Fatimah (Jurnal Usuluddin, 2007)
Youths or students are regarded as the future leaders. Currently many of them not only involved in disciplinary problems but with several alarming social problems. Some are involved in juvenile crimes such as murdering, raping and extortion. Others are involved in absenteeism from school and bullying. There are several factors contributing to social problems like lack of parental love and care, negative influence of peer groups, lack of religious education and others. Disciplinary problem is the main factor hindering the students academic achievement.